2005
DOI: 10.1021/jp045682h
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Possible Structures of Silicon Nanotubes via Density-Functional Tight-Binding Molecular Dynamics Simulations and ab Initio Calculations

Abstract: We show, computationally, that single-walled silicon nanotubes (SiNTs) can adopt a number of distorted tubular structures, representing respective local energy minima, depending on the theory used and the initial models adopted. In particular, "gearlike" structures containing alternating sp(3)-like and sp(2)-like silicon local configurations have been found to be the dominant structural form for SiNTs via density-functional tight-binding molecular dynamics simulations (followed by geometrical optimization usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 36 publications
6
34
0
5
Order By: Relevance
“…The M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 10 calculated high formation energies of the single wall CNT like single wall SiNTs [88] or the rolled-up Si (111) sheets [89] in comparison to the bulk silicon with diamond structure confirms the above argument. Several theoretical investigations have suggested the possibility of formation of silicon nanotubes based on rolled-up graphene-like sheets and predicted their structures and properties but experimental results are contrary to that [88][89][90]. Fagan et al [91] have applied the DFT and showed the similarities in the electronic and structural properties of SiNTs and CNTs.…”
Section: A N U S C R I P Tsupporting
confidence: 62%
“…The M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 10 calculated high formation energies of the single wall CNT like single wall SiNTs [88] or the rolled-up Si (111) sheets [89] in comparison to the bulk silicon with diamond structure confirms the above argument. Several theoretical investigations have suggested the possibility of formation of silicon nanotubes based on rolled-up graphene-like sheets and predicted their structures and properties but experimental results are contrary to that [88][89][90]. Fagan et al [91] have applied the DFT and showed the similarities in the electronic and structural properties of SiNTs and CNTs.…”
Section: A N U S C R I P Tsupporting
confidence: 62%
“…Radial buckling is also calculated for the armchair Si nanotubes. Small nanotubes (Si(4 4) and Si (5 5)) have high buckling with a puckered gear-like structure 47 (the gear-like structure is that of a deformed tubular shape) and nanotubes through Si(6 6) to Si (12 12) have very small buckling with a smooth CNTlike tube (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Epur et al reported a new and straightforward approach including magnesium oxide nanorods for generating the hollow silicon nanotubes [30]. Also, intensive theoretical studies based on density functional theory and molecular dynamics simulation have been conducted to investigate the possibility of the existence of silicene nanotubes [31,32] as well as the stability and geometric structure of single and double-walled silicone nanotubes [33]. Wang et al studied the stability and electronic features of silicone nanotubes.…”
Section: Introductionmentioning
confidence: 99%